Consumer responses to private nutrition signals. Issue 2 (12th February 2019) - Karamanos, Vangelis; Hobbs, Jill E.; Slade, Peter
ABSTRACT: Mandatory labelling of nutrition information with a numerical nutrition facts panel is commonly required for prepackaged food products. Recently, food manufacturers and retailers have developed simplified nutrition signals such as front-of-package labelling (e.g. the Traffic Light label) or retail shelf labels (e.g. Guiding Stars), which provide a more intuitive signal of nutritional content. Using survey data from a sample of consumers from western Canada, this paper examines consumer responses to two private nutrition labelling programs: Guiding Stars and the Traffic Light label. Consumers are more receptive to the Traffic Light label than the Guiding Stars. Ordered probit models explore the factors influencing the likelihood of using these nutrition signals. Trust in the food label, perceived difficulty of using nutrition information, nutrition knowledge, and the importance placed on nutrition influence receptively to these labels. Simplified nutrition labels are likely to complement, rather than substitute for, the existing Nutrition Facts Table.